Osteologia craniana de Nyctibiidae (Aves, Caprimulgiformes) - da Costa, Thiago Vernaschi Vieira [UNESP]; Donatelli, Reginaldo José [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2009)
The Potoos form an exclusively neotropical family of nocturnal birds distributed throughout Central and South America, except Chile, and reaching their highest diversity in the Amazon region. The seven currently recognized species are certainly among the most poorly known birds of this region. They are characterized by a distinctive mimicry of vegetal trunks, where they remain almost motionless during daytime. For this reason, their nocturnal and cryptic habits make them exceedingly difficult to study. Published accounts on behavior and natural history of the family are scarce and contributions regarding its anatomy are rare. Here we sample six of the seven currently recognized species of Nyctibiidae, including Nyctibius grandis, N. aethereus, N. griseus, N. jamaicensis, N. leucopterus and N. bracteatus, in order to conduct a detailed and illustrated description of the skull and jaw osteology. High interspecific variation in skull osteology was observed in the family. Species of this family possess a highly modified skull, adapted to their life habits, which shelters their well developed eyes and permits a large mouth opening. The bones that form the palate structure exhibit a dorsoventral flattening, particularly in the pterigoid and parasphenoid bones, with the palatine bone being a broadly developed, wing-shaped structure. In the maxilar region, near the jugal arch, there is a tooth-like projection, unique among birds, which may assist in the retention of prey upon capture. The vomer bone is highly variable within the family, showing varying numbers of rostral projections amongst species. The broad occipital region exhibits large spacing between the quadrate bones, which are vertically disposed and possess a reduced processus orbitalis. The mandible, which is flexible and elastic, has an extremely short symphyseal region and sindesmotic joints in both mandibular rami. As a family, potoos possess a highly specialized skull which provides insight into the relationship between the form of the structures and the feeding habits of the species. Furthermore, the large interspecific variation in skull morphology emphasizes the needs for taxonomic revision within the family, which at present is lumped into a single genus.
Cranial osteology of Nyctibiidae (Aves, Caprimulgiformes)
Keywords: Caprimulgiformes; Nyctibiidae; Osteology; Potoos; Skull; Aves; Nyctibius grandis